The self-other agreement of multiple informants on empathy measures and its relation to empathic accuracy. (March 2021) - Roth, Marcus; Altmann, Tobias
Abstract: Although empathy directly involves a clear counterpart and can take place only when at least two people interact with each other, only a few studies have compared self-reports with other reports. To address this gap, in the present study, we examined the extent of self-other agreement on empathy. We applied a multi-informant design with self- and other reports for the Toronto Empathy Questionnaire (TEQ) as well as a single-item measure of empathy that directly uses the term. We also included a video-based performance test based on the empathy accuracy paradigm in which participants' ability to recognize other people's emotions was measured. Analyses were based on 152 primary participants and 357 informants. As shown by the results, self-other agreement was relatively strong when the TEQ was used in contrast to directly using the word empathy in a single-item measure. Furthermore, other ratings of empathy were largely independent of participants' emotion recognition ability.